Continental European geographers and World War II. (January 2015) - Clayton, Daniel; Barnes, Trevor J.
Abstract: This special issue considers the lives and work of Continental European Geographers during World War II. There is a range of work on the complicity of American and British geographers in this global conflict, but barely any consideration of geographers in mainland Europe. The six essays collected here provide detailed biographical and regionally specific case studies of the entanglements between geography and war in France, Germany, Denmark, Hungary, Romania and The Soviet Union between 1939 and 1945. This introduction delineates this important gap in the literature on the liaison between geography, geographers and World War II, and flags a number of ways in which it might be conceptualised and contextualised. Highlights: Examines the relations between continental European geographers and World War II. Examines the relations between continental European geography and World War II. Illuminates the connections between geography and geopolitics. Presents new material on geographers' biographies (lives and work) during World War II. Demonstrates new varieties of wartime experience among geographers.